Energy + motivation - Pedersen, Lauren; Saxon, Joshua (HBR emotional intelligence series., 2023)
Push through when procrastination calls. Some days you're on fire at work; other days you're burned out and easily distracted. How can you maintain your drive, make consistent progress, and expend your energy wisely? This book will help you identify what's behind your flagging engagement and productivity-and provide the expert research and advice on what to do about it. This volume includes the work of: Annie McKee, Heidi Grant, Shawn Achor, and Elizabeth Grace Saunders. How to be human at work. The HBR Emotional Intelligence series features smart, essential reading on the human side of professional life from the pages of Harvard Business Review. Each book in the series offers proven research showing how our emotions impact our work lives, practical advice for managing difficult people and situations, and inspiring essays on what it means to tend to our emotional well-being at work. Uplifting and practical, these books describe the social skills that are critical for ambitious professionals to master.